Relationship between Sociodemographics and Nutritional Intake of FE with the Incidence of Anemia in Pregnant Women in the Sukaraja Health Center Working Area, Bandar Lampung City in 2024 - Pranata, Rizky Arya; Amalia, Amalia (CV. Rayyan Dwi Bharata, 2024)
Anemia is an important factor associated with an increased risk of maternal and child mortality. because of its adverse effects on the mother and fetus during pregnancy. pregnant women are the group most susceptible to anemia. There are various factors that can cause anemia in pregnant women such as sociodemographics and nutritional status. Sociodemographic factors can increase the occurrence of anemia in pregnancy, which consists of age, education, family income and occupation. The purpose of this study was to determine the Relationship between Sociodemographics and Fe Nutrition Intake with the Incidence of Anemia in Pregnant Women in the Sukaraja Health Center Work Area, Bandar Lampung City in 2024. Type of Quantitative Research, the design used in this study is observational analytic with a cross-sectional approach. The population and sample in this study were all pregnant women with anemia recorded from January - May 2024, totaling 104 respondents. The sampling technique in this study was simple random sampling. Based on statistical tests, it is known that the p-value is 0.000 or p-value 0.05, which means that there is a relationship between sociodemographics and iron nutrient intake with the incidence of anemia in pregnant women in the Sukaraja Health Center Work Area, Bandar Lampung City in 2024. The results of this study are expected to be used as additional information to overcome the causes of anemia in pregnant women, namely sociodemographics and iron nutrient intake.